Improving the Knowledge of Tanjung Bubuk Community at Palembang Regarding Plastic Biocomposites from Plastic Waste-Kapok Fiber - Rahmatullah; Rizka Wulandari Putri; Prahady Susmanto; Harry Waristian; Alek Al Hadi; Muhammad Rendana; Selpiana (Jurnal Pengabdian Mitra Indonesia, 2026)
Plastic biocomposites play a significant role in reducing environmental impacts as an alternative to conventional plastics due to their more readily biodegradable nature. Plastic biocomposites can be made using a mixture of conventional plastic waste and kapok fiber through certain stages. The purpose of this community service is to increase public knowledge about how to process plastic waste and kapok fiber as raw materials for plastic biocomposites. Data collection techniques were carried out by providing an explanation of the procedure for making plastic biocomposites, followed by filling out a questionnaire about the level of understanding of the material provided. Based on the results of the survey through filling out the questionnaire before and after the activity was carried out, many residents did not know what plastic biocomposites were and only learned and understood after the activity was carried out.